The role of error in organizing behaviour. Issue 5 (7th October 2003) - Rasmussen, J
Abstract : During recent years the significance of the concept of human error has changed considerably. The reason for this has partly been an increasing interest of psychological research in the analysis of complex real life phenomena, and partly the changes of modern work conditions caused by advanced information technology. Consequently, the topic of the present contribution is not a definition of the concept or a proper taxonomy. Instead, a review is given of two professional contexts for which the concept of error is important. Three cases of analysis of human–system interaction are reviewed: (1) traditional task analysis and human reliability estimation; (2) causal analysis of accidents after the fact, and (3) design of reliable work conditions in modern sociotechnical systems. It is concluded that "errors" cannot be studied as a separate category of behaviour fragments; the object of study should be cognitive control of behaviour in complex environments.